tan⁡θ+sec⁡θ−1tan⁡θ−sec⁡θ+1=

tanθ+secθ1tanθsecθ+1=

  1. A

    1sinθcosθ

  2. B

    1+sinθcosθ

  3. C

    -cosθ1+sinθ

  4. D

    cosθ1+sinθ

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    tanθ+secθ1tanθsecθ+1=sinθ+1cosθsinθ1+cosθ

    =2sinθ2cosθ2+2sin2θ22sinθ2cosθ22sin2θ2=cosθ2+sinθ2cosθ2sinθ2=cosθ2+sinθ22cos2θ2sin2θ2=1+sinθcosθ=1sin2θcosθ(1sinθ)=cosθ1sinθ

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.